Online Leave System Kolej Poly Tech Mara Bangi - Arifin, Marina Murni (2004)
At present, leave application procedures is being manually performed at Kolej Poly Tech MARA Bangi. Hence, such procedure has not only created a time-consuming process in the approval of the leave application of the staff, but also human mistakes problems like a lost of the application form.Bearing in mimd the problem arise due to such painstaking procedure, a proposed system of Online Leave System (OLS) is created with the aim of building a communication platform between the departments and its staff at Kolej Poly-Tech MARA Bangi. The main objective of this system is to help the Human Resource department to handle staffs information specifically in providing leave applications electronically. One special feature of the Online Leave System is the administration interface that is designed for the System Administrator to manage the database storing the staff information and details of leave applications. It makes the Online Leave System flexible and compatible with any new arrangement of the company. The system provides all staff with direct access, from their desktop and in a secure environment, to current information on 1eave entitlements, 1eave applications, etc The Online Leave System allows authorized staff at the departmental level to electronically enter and maintain 1eave. In addition, units will b e able to develop and maintain very detailed leave records. The new system users cm simply access the system via the Internet with their unique login names and passwords. It requires no special hardware or software installation, except the use of a web browser. To use the system, an employee simply needs a Leave System account, which is usually created by the Human Resource department when the employee is hired. Each month the appropriate number of accrued leave is automatically added to the leaves balance and the employee can enter any leave,which is to be taken (annual, medical) into the system. The leave requests are then automatically sent to the employee's supervisor for approval. Once the supervisor approves the leave requests, the appropriate number of day is added to or subtracted from the employee's leave balance so that a running total is kept.While this may sound complicated, it's actually an easy, paperless way to track an employee's leave balance. There are no paper forms involved and no mistakes to be made in adding or subtracting leave time. Hence, the Leave System also provides a convenient way for each employee to check his or her own current balance from his workstation and the reports the system can generate m ake end-of-year 1eave close-outs quick and easy. The system is mainly made up of Lotus Notes Domino R5 and Java' Script codes. All of the information is stored in the database. As a result, all information is retrieved dynamically from the database.